Maternal Critical Care: The Story Behind the Numbers. Issue 3 (24th September 2022) - Toledo, P.; Nelson, L.; Stey, A.
Abstract : ( Analg . 2022;134:578–580) In 2014, 50, 000 maternal patients experienced severe maternal morbidity (SMM) and about 700 of these patients died. Postpartum and antepartum units do not have the staff required for intense patient monitoring, resulting in admission to the intensive care unit (ICU). An admission to the ICU postpartum results in separation of the mother from the infant, increasing the risk of postpartum depression, decreased bonding with the infant, and delayed initiation of breast-feeding. Given the rarity of maternal mortality, determining outcomes from maternal morbidity allows for greater quality assessment and improvement.